8+3(-2m-4)=

Simple and best practice solution for 8+3(-2m-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+3(-2m-4)= equation:


Simplifying
8 + 3(-2m + -4) = 0

Reorder the terms:
8 + 3(-4 + -2m) = 0
8 + (-4 * 3 + -2m * 3) = 0
8 + (-12 + -6m) = 0

Combine like terms: 8 + -12 = -4
-4 + -6m = 0

Solving
-4 + -6m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -6m = 0 + 4

Combine like terms: -4 + 4 = 0
0 + -6m = 0 + 4
-6m = 0 + 4

Combine like terms: 0 + 4 = 4
-6m = 4

Divide each side by '-6'.
m = -0.6666666667

Simplifying
m = -0.6666666667

See similar equations:

| -7(3p+4)-37=2(2p+5) | | 1+1+1+1+1*0=x | | -13-2b=b-7 | | -3p+8=5-(8p+4) | | 2-8(4y-7)= | | (2.35+2.71i)-(4.91+3.32i)=0 | | 1x+7=3x+1 | | n/5=1.6 | | 6(t-2)+8t=7(2t+4)-9 | | 7x+3y+x=16+3 | | 4+(6-7p)-2= | | 7x+1=5x-3 | | 3(x+9)=18 | | -14b+7a+2a=-5b | | x+(x+28)(2x-38)=652 | | 2y^3-13y^2+6y=0 | | x^3+x^2+2x+2=0 | | 16v^6w^7+22v^2w^6y^4= | | 7x-10=15+2x | | x-42=51 | | 3mx^2-2mx+2=x(6-5x) | | 5x-4y+9y=-15x+5 | | x+8=29 | | 0.6x+7=21 | | 8m-15m=56 | | 80z^8-45z^6=0 | | 3d-5=7d-12 | | 0.5x-4=6 | | -2t+4t-7s=9s | | 0.4x+10=20 | | 8+3(s-4t)= | | -4y-3x-x=-16y |

Equations solver categories